2020
DOI: 10.3389/fphys.2020.535722
|View full text |Cite
|
Sign up to set email alerts
|

Post-exercise Effects and Long-Term Training Adaptations of Hormone Sensitive Lipase Lipolysis Induced by High-Intensity Interval Training in Adipose Tissue of Mice

Abstract: Although studies have proven that high-intensity interval training (HIIT) shows a comparable effect to moderate-intensity continuous training (MICT) on reducing body fat, especially visceral fat, the mechanism is still unclear. Since MICT consumes more fat during exercise, the mechanism of HIIT weight loss may be related to post-exercise effects, long-term adaptive changes, and hormone sensitive lipase (HSL). The objective of this study was to compare the post-effects of acute exercise, long-term adaptive chan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
12
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 49 publications
1
12
1
Order By: Relevance
“…Another reasonable hypothesis is that due to the intense load of HIIT, during the recovery period, adipose tissue would release more lipid for gluconeogenesis, ketogenesis or tissue healing [ 24 ], which suggests that HIIT promotes adaptive catabolism of adipose tissue. Studies have verified the increase in β-AR and lipolysis in adipocytes after long-term HIIT [ 26 , 28 ], supporting the hypothesis of adaptive changes in SNS lipolytic pathway. As mentioned earlier, when facing catabolic stress, OP individuals are more likely to show adaptation (fat is lost easily), while OR individuals are more likely to maintain homeostasis [ 35 , 36 ].…”
Section: Discussionmentioning
confidence: 57%
See 4 more Smart Citations
“…Another reasonable hypothesis is that due to the intense load of HIIT, during the recovery period, adipose tissue would release more lipid for gluconeogenesis, ketogenesis or tissue healing [ 24 ], which suggests that HIIT promotes adaptive catabolism of adipose tissue. Studies have verified the increase in β-AR and lipolysis in adipocytes after long-term HIIT [ 26 , 28 ], supporting the hypothesis of adaptive changes in SNS lipolytic pathway. As mentioned earlier, when facing catabolic stress, OP individuals are more likely to show adaptation (fat is lost easily), while OR individuals are more likely to maintain homeostasis [ 35 , 36 ].…”
Section: Discussionmentioning
confidence: 57%
“…This phenomenon may be related closely to the difference between obesity phenotypes in adipose catabolism. Previous experiments have found that the fat loss effect of HIIT is related to the activation lipolysis [ 26 28 , 31 ]. Because gene polymorphisms underlie individual differences in food intake, PA and adipose metabolism, we hypothesised that OP and OR individuals show different adaptive changes to HIIT, especially in lipolysis regulated by the SNS.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations